The task of basing ethics on kart-otto apel and in convergent ethics - Maliandi, Ricardo (Acta Bioethica, 2009)
The present article sums up the task of the transcendental a priori basis developed by the ethics of discourse elaborated by Karl-Otto Apel. From a personal position, he resorts to this theoretical proposal and the contributions that were realized in parallel by Nicolai Hartmann, during the last century in the spirit of proposing a convergent ethics as a variation and complement to Apel´s ethics of discourse.